2020
DOI: 10.3390/ijerph17124298
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Time-Invariant Biomarkers for Non-Genotoxic Hepatocarcinogen Assessment

Abstract: Non-genotoxic hepatocarcinogens (NGHCs) can only be confirmed by 2-year rodent studies. Toxicogenomics (TGx) approaches using gene expression profiles from short-term animal studies could enable early assessment of NGHCs. However, high variance in the modulation of the genes had been noted among exposure styles and datasets. Expanding from our previous strategy in identifying consensus biomarkers in multiple experiments, we aimed to identify time-invariant biomarkers for NGHCs in short-term exposure styles and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…A transcriptomic biomarker (or signature) is a set of transcripts induced by a specific event that can be useful in chemical hazard assessment, as well as clinical diagnostic, prognostic, and therapeutic purposes [427,428]. Transcriptomic analyses are being improved to identify signatures associated with specific chemical classes and modes of action and may eventually assist in the identification of NGTxC using in vitro [429], and short-term in vivo rodent data [430]. Transcriptomic approaches [431] are data rich, and they offer the possibility of using the same sample to assess multiple signatures in parallel in a screening strategy.…”
Section: Consideration Of Multiple Dmr/genes In Parallel As Markers Of Key Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…A transcriptomic biomarker (or signature) is a set of transcripts induced by a specific event that can be useful in chemical hazard assessment, as well as clinical diagnostic, prognostic, and therapeutic purposes [427,428]. Transcriptomic analyses are being improved to identify signatures associated with specific chemical classes and modes of action and may eventually assist in the identification of NGTxC using in vitro [429], and short-term in vivo rodent data [430]. Transcriptomic approaches [431] are data rich, and they offer the possibility of using the same sample to assess multiple signatures in parallel in a screening strategy.…”
Section: Consideration Of Multiple Dmr/genes In Parallel As Markers Of Key Eventsmentioning
confidence: 99%
“…Efforts for the identification of signatures of NGTxC based on rodent short-term in vivo experiments using genes with less dynamic expression changes are also progressing. Using machine learning and publicly available hepatic datasets Huang et al [430] exposed male Sprague Dawley rats to chemicals for 1 to 28 days and identified a signature of 9 genes (upregulation of Akr7a3, Aqp7, Cdc2a, and Cdkn3, and downregulation of A2m, Ca3, Cyp2c11, Ntf3, and Sds) for which expression levels remain unaltered through time and that can be measured in 3-day exposure experiments to predict NGTxC and other hepatic diseases. By combining gene expression and DNAm analyses, Ito et al [436] identified four genes (Ldlrad4, Proc, Cdh17, and Nfia) silenced and hypermethylated after 28 days of exposure to non-genotoxic hepatocarcinogens (carbon tetrachloride, thioacetamide, methapyrilene hydrochloride) in rats, that remained silenced until the end of the 90-day experiment.…”
Section: Consideration Of Multiple Dmr/genes In Parallel As Markers Of Key Eventsmentioning
confidence: 99%
“…CEBPB is associated with the development of various tumors, including osteosarcoma, gastric cancer, HCC, glioblastoma, and human acute myeloid leukemia (Lu et al, 2019 ; Jinesh et al, 2020 ). A2M was identified as a key gene associated with various tumors, including non–small cell lung cancer, bladder cancer, osteosarcoma, and HCC (Ma et al, 2019 ; Huang et al, 2020 ). TUBA1B was related to breast cancer, HCC, and Wilms tumor (Lou et al, 2020 ; Tian et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This theme investigates the potential risks and benefits associated with disease control [ 33 , 34 , 35 , 36 , 37 ]. Data mining is a technique that allows for the analysis of large data sets, enabling the identification of previously unknown relationships and new structures.…”
Section: The Organization Of This Special Issuementioning
confidence: 99%